An efficient algorithm for congestion control in highly loaded DiffServ/MPLS networks - Krile, Srećko (Array, 2009)
Abstract: The optimal QoS path provisioning of coexisted and aggregated traffic in networks is still demanding problem. All traffic flows in a domain are distributed among LSPs (Label Switching Path) related to N service classes, but the congestion problem of concurrent flows can appear. As we know the IGP (Interior Getaway Protocol) uses simple on-line routing algorithms (e.g. OSPFS, IS-IS) based on shortest path methodology. In QoS end-to-end provisioning where some links may be reserved for certain traffic classes (for particular set of users) it becomes insufficient technique. On other hand, constraint based explicit routing (CR) based on IGP metric ensures traffic engineering (TE) capabilities.